BIODIVERSITY OF PLANTS AND NATURAL HABITATS IN THE VICINITIES OF ARAPYA BAY, ROPOTAMO NATURAL RESERVE, ALEPU BEACH, SINEMORETS AND SILISTAR CAPE (BULGARIAN SOUTHERN BLACK SEA COAST) - D. Dimitrov; V. Vutov (Trakia Journal of Sciences)
The flora in the vicinities of Arapya Bay, Alepu beach, Sinemorets and Silistar cape of the Bulgarian Black Sea coast (which includes three beach zones and two protected natural areas) is rich in rare psammophytic and halophytic species: Hypecoum ponticum Velen., Pancratium maritimum L., Silene thymifolia Sm., Eryngium maritimum L., Limonium latifolium (Sm.) Kuntze, Tulipa thracica Davidov, Centaurea arenaria M. Bieb., Trachomitum venetum (L.) Woodson and Maresia nana (DC.) Batt. Within these areas some Mediterranean geo elements reach their northernmost point: Reichardia picroides (L.) Roth and Romulea linaresii Parl. All of the species mentioned above have been included in the Red List of Bulgarian vascular plants (1) The Tulipa thracica Davidov species fall under a Critically Endangered (CR) category. Nine species have an Endangered (EN) status: Hypecoum ponticum Velen., Pancratium maritimum L., Silene thymifolia Sm., Eryngium maritimum L., Trachomitum venetun (L.) Woodson, Reichardia picroides (L.) Roth, Cistus salviifolius L., Verbascum bugulifolium Lam. and Serapias vomeracea (Burm.) Briq. Six species fall under a Vulnerable (VU) category: Limonium latifolium (Sm.) Kuntze, Centaurea arenaria M. Bieb., Maresia nana (DC.) Batt. and Romulea linaresii Parl., Limodorum abortivum (L.) Schwarz and Orchis papilionacea L. Under a Least Concern (LC) are the following species: Fritillaria pontica Wahlenb. and Mespilus germanica L. Legally protected by (2) are: Pancratium maritimum L., Eryngium maritimum L., Limonium latifolium (Sm.) Kuntze, Tulipa thracica Davidov, Centaurea arenaria M. Bieb., Trachomitum venetum (L.) Woodson, Maresia nana (DC.) Batt, Reichardia picroides (L.) Roth, Romulea linaresii Parl., Verbascum bugulifolium Lam., Cistus salviifolius L., Serapias vomeracea (Burm.) Briq., Limodorum abortivum (L.) Schwarz, Orchis papilionacea L., Fritillaria pontica Wahlenb. In addition, there are five species from the Orchidaceae family with different conservation status: the Endangered Serapias vomeracea (Burm.) Briq., the Vulnerable Limodorum abortivum (L.) Schwarz and Orchis papilionacea L. and two species from the CITES convention - Orchis purpurea Huds.and Orchis morio L. Three habitats were with an Endangered Conservation status: 01B1 Pontic sand beach annual communities, 02B1 Pontic embryonic dunes and 04B1 Southwestern Pontic fixed dunes (3).